The prophet and the blind man: quran stories for little hearts - Khan, Saniyasnain (Goodword Books India, 2002)
"The Prophet and the Blind Man" is a story about the Prophet Muhammad's encounter with a blind man who seeks guidance. Initially, the Prophet is distracted by the presence of wealthy leaders, but he later realizes the importance of inclusivity and compassion, emphasizing that everyone deserves respect and attention, regardless of their social status.